ANALYSIS OF AIR POLLUTION CAUSED BY VEHICLES ON ARTERIAL ROADS IN BOGOR CITY - Annisa Aulia Rahma; Nurlaela Kumala Dewi; Syafrianita (Organisasi Kreatif Indonesia Emas, 2025)
With the growth in the number and types of vehicles in Bogor City, there are new conveniences and challenges. One of them is the large number of vehicle exhaust emissions that mix with each other in the air, causing air pollution caused by vehicles passing through arterial roads and causing congestion. This study aims to determine how much pollution caused by vehicles, especially those generated on arterial roads in Bogor City and is expected to help related parties to take mitigation actions. This research was conducted using the VKT (Vehicle Kilometer-Traveled) method to calculate vehicle pollution and the Simple Box Model to determine the amount of types of emissions produced. The vehicle exhaust emissions produced are quite high, therefore mitigation measures need to be taken.